Adjoint invariants of Frobenius kernels of GL(m) and elements of the center of Dist(GL(m)). Issue 12 (2nd December 2019) - Marko, František
Abstract: The first goal of this article is to explicitly describe how to translate adjoint invariants K [ G r ] G of the Frobenius kernel Gr of the general linear group G = GL ( m ) to elements of the center of the distribution algebra of Gr . The second goal is to provide a characterization of K [ G r ] G and to find algebra generators of K [ G 1 ] G in the case when G = GL ( 2 ) .